SINTESIS KEPEMIMPINAN TRANSFORMASIONAL DAN DIGITAL BERBASIS ARTIFICIAL INTELLIGENCE DALAM PENGEMBANGAN MODEL INOVASI ORGANISASI PENDIDIKAN ISLAM: PENDEKATAN INTERDISIPLINER - Afif Syaiful Mustofa; Mukhamad Ilyasin (STKIP Subang, 2026)
This study aims to develop an interdisciplinary leadership model that integrates transformational leadership, digital leadership based on Artificial Intelligence (AI), and Islamic values to foster organizational innovation in Islamic educational institutions. This research employs a qualitative approach with a library research design through a systematic literature review of reputable academic sources. The findings indicate that transformational leadership plays a crucial role in building an innovative culture through vision, motivation, and human resource empowerment, while digital leadership enhances organizational capabilities in utilizing technology and data for adaptive decision-making. AI functions as an enabler that improves organizational innovation through data analysis and strategic prediction, whereas Islamic values serve as an ethical foundation to balance technological advancement and humanistic principles. The integration of these three dimensions results in a comprehensive, adaptive, and value-oriented leadership model. This study contributes theoretically to the development of Islamic educational leadership in the digital era and provides practical implications for educational leaders in managing sustainable and ethical organizational innovation.